2018
DOI: 10.5089/9781484361535.001
|View full text |Cite
|
Sign up to set email alerts
|

Tax Revenue Mobilization Episodes in Emerging Markets and Low-Income Countries: Lessons from a New Dataset

Abstract: How do countries mobilize large additions to tax revenue-defined as an average increase in the tax-to-GDP ratio of 0.5 percent per year over three years or more? To answer this question, we build a novel dataset covering 55 episodes of large tax revenue increases in low-income countries and emerging markets. We find that: (i) reforms of indirect taxes and exemptions are the most common tax policy measures; (ii) multi-pronged tax administration reforms often go hand in hand with tax policy measures; and (iii) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Our research revealed that a high-level political commitment and buy-in from all stakeholders played a crucial role for success. These findings are further discussed in the follow-up papers on cases studies Akitoby, Baum, et al 2019;. For example, Georgia's comprehensive tax reform was feasible only after the country had reached a high degree of dysfunction, triggering a revolution.…”
Section: Causality Cannot Be Inferredmentioning
confidence: 93%
See 3 more Smart Citations
“…Our research revealed that a high-level political commitment and buy-in from all stakeholders played a crucial role for success. These findings are further discussed in the follow-up papers on cases studies Akitoby, Baum, et al 2019;. For example, Georgia's comprehensive tax reform was feasible only after the country had reached a high degree of dysfunction, triggering a revolution.…”
Section: Causality Cannot Be Inferredmentioning
confidence: 93%
“…Moreover, applying tax reform lessons to a specific country calls for a selective adaptation as equity and political economy factors can become serious implementation obstacles. Three follow-up papers discuss cases studies in more detail Akitoby, Baum, et al 2019;, which will help public authorities to tailor their revenue mobilization design to country successes with similar political or economic backgrounds.…”
Section: Tax Policy and Administration Reforms Behind Revenue Mobilizmentioning
confidence: 99%
See 2 more Smart Citations
“…and low-income countries (LICs) have significantly increased tax revenue collection over a medium-term period. As highlighted inAkitoby et al (2018), several fragile states and LICs have sustained increases in their tax-to-GDP ratios, even under unstable Source: World Economic Outlook database; and IMF staff estimates.…”
mentioning
confidence: 99%